Diet in the early years of life influences cognitive outcomes at 10 years: a prospective cohort study. (14th August 2013) - Nyaradi, Anett; Li, Jianghong; Hickling, Siobhan; Whitehouse, Andrew JO; Foster, Jonathan K; Oddy, Wendy H
Abstract Aim The aim of this study was to investigate the association between diet during the first 3 years of life and cognitive outcomes at 10 years of age. Methods The Raine Study is a longitudinal study of 2868 children and their families. Based on the foods reported to be eaten at age one, two and three, an Eating Assessment in Toddlers diet score was developed, consisting of seven components. Cognition was measured by the Peabody Picture Vocabulary Test‐III (PPVT‐III) and the Raven's Coloured Progressive Matrices at the 10‐year follow‐up. Associations were assessed in multivariate regression models. Results A higher Eating Assessment in Toddlers diet score at age one was associated with higher PPVT‐III [β = 0.12 (0.05, 0.19), p = 0.001] and Raven's Coloured Progressive Matrices scores [β = 0.17 (0.02, 0.33), p = 0.025] at age ten after adjustments. Increased fruit consumption at age one was positively associated, while increased sweetened beverage consumption was negatively associated with cognitive development. Dairy consumption at ages two and three had positive associations with the PPVT‐III and at age two with the Raven's Coloured Progressive Matrices. Conclusion A better diet quality during the early years of life may have a positive effect on cognitive ability later in childhood.